Interactive effects between paylean (ractopamine⋅HCl) and dietary L-carnitine on finishing pig growth performance and carcass characteristics - B W James; K Q Owen; T E Lawrence; Michael D Tokach; Robert D Goodband; Jim L Nelssen; John A Unruh; Steven S Dritz (Kansas Agricultural Experiment Station Research Reports, 2002)
Growth performance, carcass characteristics, and meat quality were evaluated from 126 pigs fed combinations of Paylean and L-carnitine arranged in a 3 × 3 factorial. Dietary L-carnitine (0, 25, or 50 ppm) was fed from 74 lb until slaughter, and Paylean (0, 4.5, or 9 g/ton) was fed the last 4 weeks prior to slaughter. These results suggest that Paylean, but not L-carnitine, increases ADG and improves F/G. However, L-carnitine enhances meat quality by improving visual color, L* (darker color), b* (less yellow), a*/b*, and Hue angle (more red and less orange) when fed with Paylean. L- carnitine also decreases drip loss and saturation index (vividness or intensity) and increases 24-h pH.; Swine Day, Manhattan, KS, November 14, 2002
Keywords: Swine day; 2002; Kansas Agricultural Experiment Station contribution; no. 03-120-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 897; Carnitine; Paylean; Meat Quality; Swine